2023
DOI: 10.3390/resources12100123
|View full text |Cite
|
Sign up to set email alerts
|

Biosolids-Derived Biochar Improves Biomethane Production in the Anaerobic Digestion of Chicken Manure

Soulayma Hassan,
Tien Ngo,
Leadin S. Khudur
et al.

Abstract: Anaerobic digestion has attracted great interest for use in the management of organic wastes and the production of biomethane. However, this process is facing challenges, such as a high concentration of ammonia nitrogen, which affects the methanogenesis process and, thus, the production of methane. This study investigates the use of biosolid-derived biochar for mitigating ammonia stress and improving methane production during the anaerobic digestion of chicken manure, using both pristine biochar and biochar mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
(114 reference statements)
1
4
0
Order By: Relevance
“…To investigate this potential in a configuration applicable to a commercial scale, BMP and semi-continuous digestion using source-separated wastewater were undertaken. In this study, initial BMP showed biogas yields approaching those of similar tests in the literature [25,110,111] but lower than expected biogas and methane yields under semi-continuous feeding conditions. This may be caused by the combination of operating conditions, inoculum, and feedstock composition unique to this study.…”
Section: Source-separated Wastewater Potentialsupporting
confidence: 60%
See 4 more Smart Citations
“…To investigate this potential in a configuration applicable to a commercial scale, BMP and semi-continuous digestion using source-separated wastewater were undertaken. In this study, initial BMP showed biogas yields approaching those of similar tests in the literature [25,110,111] but lower than expected biogas and methane yields under semi-continuous feeding conditions. This may be caused by the combination of operating conditions, inoculum, and feedstock composition unique to this study.…”
Section: Source-separated Wastewater Potentialsupporting
confidence: 60%
“…This was performed by adding new substrate to the existing reactor sludge once biogas production had ceased [57,58]. Acclimatisation was especially important for the digesters containing biochar, as it is necessary for microbes to colonise pores in the biochar [25]. For the sequential runs, each reactor was fed the same quantity of substrate as originally fed and biochar in the same 2:1 gTS ratio as appropriate.…”
Section: Biomethane Potential Testsmentioning
confidence: 99%
See 3 more Smart Citations